2015
DOI: 10.1007/s13277-015-3547-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of SOX17 is associated with tumor progression and poor prognosis in breast cancer

Abstract: The SOX17 (SRY-related HMG-box) transcription factor is involved in a variety of biological processes and is related to the tumorigenesis and progression of multiple tumors. However, the clinical application of SOX17 for breast cancer prognosis is currently limited. The aim of this study was to investigate the clinicopathologic and prognostic significance of SOX17 expression in human breast cancer. qPCR and western blot assays were performed to measure the expression of SOX17 in breast cancer cell lines and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Thus, it is necessary to develop new prognostic tools and effective therapeutics that may be bene cial for improving the clinical management of oral cancer. In the recently studies, application of prognostic biomarkers has directed the research in the tumor studies [25,26]. For example, Xu et al have found that bulin-5 could serve as an independent prognostic factor and promote the proliferation and invasion in glioma [27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to develop new prognostic tools and effective therapeutics that may be bene cial for improving the clinical management of oral cancer. In the recently studies, application of prognostic biomarkers has directed the research in the tumor studies [25,26]. For example, Xu et al have found that bulin-5 could serve as an independent prognostic factor and promote the proliferation and invasion in glioma [27].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Fu et al demonstrated that SOX17 expression was downregulated and correlated with the poor prognosis of breast cancer. 21 MicroRNA-106b, another example, has been proved to be involved in the recurrence of breast cancer and to act as an independent prognostic factor in patients with breast cancer. 22 Jerzak et al reported that the thyroid hormone receptor α ( THRα ) represented an efficient prognostic biomarker in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Yeh et al reported that granulin is an important prognostic biomarker and potential therapeutic target in breast cancer [22]. Fu et al indicated that SRY-related HMG-box ( SOX17 ) is associated with breast cancer progression and can act as a useful prognostic biomarker [23]. Pelkonen et al claimed that hepsin and TMPRSS3 can serve as prognostic markers in breast cancer [24].…”
Section: Discussionmentioning
confidence: 99%